Model Pembelajaran Quantum Teaching Berbasis Multimedia sebagai Bentuk Inovasi Active Learning - Novi Mayasari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2017)
Multimedia-based quantum teaching is one of active learning instructional innovation. The active learning concept of multimedia-based quantum teaching is implemented through the framework of TANDUR (Grow, Nurture, Name, Demonstrate, Repeat, and Celebrate) and it uses multimedia as the learning media. Multimedia is implemented in the form of audio-visual with macromedia flash player application containing subject matter and educational game called as Electronic Puzzle. Multimedia-based quantum teaching is a form of active learning innovation that can be implemented by educators or teachers during the learning process. It is expected to help educational professionals, especially teachers, to enhance the students' motivation in order to help them achieve the expected learning goals.